Estimated collective effective dose to the population from nuclear medicine diagnostic procedures in Croatia: A comparison of 2010 and 2015. - Ivana Kralik; Mario Štefanić; Hrvoje Brkić; Gordan Šarić; Stanko Težak; Svjetlana Grbac Ivanković; Neva Griotto; Damir Štimac; Otmar Rubin; Tamer Salha; Zrinka Ivanišević; Slaven Jurković; et al. (PLoS ONE, 2017)
Objective This study presents national surveys of patient exposure from nuclear medicine (NM) diagnostic procedures in 2010 and 2015 in the Republic of Croatia. Methods The survey was performed according to the European Commission Dose DataMed (DDM) project methodology. 28 most frequent NM diagnostic procedures were identified. Data about frequencies of procedures and average administered activities of radioisotopes used in those procedures were collected. Average administered activities were converted to effective doses according to the dose conversion coefficients. Then the collective effective dose to the population and an effective dose per capita were calculated based on the number of the most frequent NM diagnostic procedures and the average effective dose per procedure. Results In 2010, 41200 NM diagnostic procedures led to 146.7 manSv collective effective dose to the population and in 2015, 42000 NM diagnostic procedures led to 146.8 manSv collective effective dose to the population. The frequencies of NM diagnostic procedures were 9.7 and 9.8 annually per 1000 population with 34.1 μSv and 34.2 μSv effective dose per capita for 2010 and 2015, respectively. The main contributors to the annual collective dose from NM in Croatia are examinations of the bone, heart, thyroid and PET/CT tumour diagnostic. Average administered activities have not changed considerably from 2010 to 2015. Nevertheless, within the frequency of some of the procedures, significant changes were found in five-year period. Conclusions Frequencies, average administered activities and collective effective dose to the population from NM diagnostic procedures in Croatia are comparable to the values reported by other European surveys. Changes were found between 2010 and 2015 and we intend to perform this study periodically to identify possible trends, but also to raise awareness about the potential dose optimization.